Removal Of Colour From Pulp And Paper Mills Effluent Using Enzymatic Treatment And Advanced Oxidation Processes - Mazraehshahi, Samaneh Karimi (2009)
This research is investigated the efficiency of Advanced Oxidation Processes (AOP) (Fenton and photo-Fenton processes), enzymatic treatment, and combined enzymatic/ AOP sequences on colour removal of soda and Chemical Mechanical Pulping (CMP) effluent samples from two major pulp and paper mills in Iran. In addition, the effect of AOP as a pre-treatment unit and post-treatment unit in conjuction with biological treatment, in the combined treatment system, were investigated. Results indicated that, under all circumstances, Fenton process using UV irradiation (photo-Fenton) was found to be more efficient in the degradation of effluent components, compared to the dark reaction.UPLOAD Regarding the enzymatic treatment, two kinds of fungal enzymes; Laccase (EC: 1.10.3.2) from Terametes Versicolour and Versatile Peroxidase (EC: 1.11.1.7) from Bjerkandera adusta were selected and used. In order to determine the effect of enzyme dosage on the overall efficiency of decolourization, experiments were carried out at 2 dosages (1 mg & 2 mg) for each enzyme. To evaluate the effect of external mediator on the enzyme based degradations, each enzyme was applied on the effluent samples, one with the presence of external mediator, and the other, without it, while the other conditions were the same.